South Asian Economics Students’ Meet (SAESM): Twenty years on alumni tracer survey and impact assessment report - Pal, Ipshita; Choudhury, Homagni; Mahzab, Moogdho (World Bank, 2025)
The South Asian Economics Students’ Meet (SAESM) started in 2004 as a regional forum to bring together undergraduate economics students from various South Asian nations. SAESM as a platform continues to identify leadership capacity, provide opportunities for an early and transformative exposure to the value of regional cooperation, and expand a network of like-minded intellectuals and leaders who remain invested in the region’s future. This study, commissioned by the World Bank South Asia Regional Integration Program and the South Asia Chief Economist Office, examines whether and how SAESM shaped ideas, attitudes, and aspirations and fostered knowledge exchange, skill development, and networking opportunities among student participants and organizers. It also documents SAESM's overall impact on regional cooperation efforts and human capital investment in South Asia.